EFFECT OF INTRAUTERINE IMMUNOTHERAPY ON UTERINE CELLULAR DYNAMICS AND CONCEPTION RATE IN ENDOMETRITIC COWS - SARMA, D K; SINGH, BALRAJ; SINGH, M P; TIWARY, B K; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
The efficacy of three intrauterine (IU) immunomodulators was investigated in endometritis of cross bredcows. ·Forty endometritic cows were divided into 4 groups (n=10) and marked as T1, T2, T3 and T4 T1 cows receivedE. coli lipopolysaccharide (LPS). Oyster Glycogen (OG) and Autologus Plasma (AP) were used in group T2 and T3,respectively. T4 was kept as control with single infusion of 60ml Phosphate Buffer Solution (PBS, pH-7.2). After24 hours of treatments significant (P
Keywords: Cows; Endometritis; Intrauterine lmmunotherapy